Overview of saxagliptin efficacy and safety in patients with type 2 diabetes and cardiovascular disease or risk factors for cardiovascular disease - Toth PP (Vascular Health and Risk Management, 2014)
Peter P Toth1,2 1CGH Medical Center, Sterling IL, USA, 2Johns Hopkins University School of Medicine, Baltimore, MD, USA Abstract: Most individuals with type 2 diabetes mellitus have or will develop multiple independent risk factors for cardiovascular disease, particularly coronary artery disease (CAD). CAD is the leading cause of morbidity and mortality among individuals with type 2 diabetes mellitus, and treating these patients is challenging. The risk of hypoglycemia, weight gain, or fluid retention with some diabetes medications should be considered when developing a treatment plan for individuals with a history of CAD or at risk for CAD. Dipeptidyl peptidase-4 inhibitors are oral antihyperglycemic agents that inhibit the breakdown of the incretin hormones glucagon-like peptide-1 and glucose-dependent insulinotropic polypeptide, resulting in increased glucose-dependent insulin secretion and suppression of glucagon secretion. Saxagliptin is a potent and selective dipeptidyl peptidase-4 inhibitor that improves glycemic control and is generally well tolerated when used as monotherapy and as add-on therapy to other antihyperglycemic medications. This review summarizes findings from recently published post hoc analyses of saxagliptin clinical trials that have been conducted in patients with and without a history of cardiovascular disease and in patients with and without various risk factors for cardiovascular disease. The results show that saxagliptin was generally well tolerated and consistently improved glycemic control, as assessed by reductions from baseline in glycated hemoglobin, fasting plasma glucose concentration, and postprandial glucose concentration, regardless of the presence or absence of baseline cardiovascular disease, hypertension, statin use, number of cardiovascular risk factors, or high Framingham 10-year cardiovascular risk score. Keywords: cardiovascular disease, dipeptidyl peptidase-4 inhibitors, incretin, saxagliptin, type 2 diabetes mellitus